Interchangeability of delta subunits of RNA polymerase from different species of the genus Bacillus. - Achberger, E C (1982)
RNA polymerase was purified from five species of Bacillus, including Bacillus subtilis. Each polymerase had a subunit composition analogous to that reported for B. subtilis, i.e., beta beta '2 alpha sigma delta omega 1 omega 2. The delta subunits from the B. subtilis and Bacillus thuringiensis polymerases were interchangeable, as judged from their effects on promoter selection in the polymerase binding assay.